Pd(II)-Schiff base complexes: Synthesis, characterization, Suzuki-Miyaura and Mizoroki-Heck cross-coupling reactions, enzyme inhibition and antioxidant activities - Turan, Nevin; Buldurun, Kenan; Bursal, Ercan; Mahmoudi, Ghodrat (Elsevier Science Sa, 2022)
In this study, new coordination complexes (1a-1e) of Pd(II) with Schiff base ligands were synthesized and characterized by elemental analysis, magnetic susceptibility, molar conductivity, FT-IR, H-1-C-13 NMR spectroscopy, UV-vis spectroscopy, and mass spectrometry techniques. The ligands formed only 1:2 complexes with the Pd(II) except for the complex 1e . The thermal analysis of the complexes was performed by the TGA technique. The antioxidant potential, enzyme inhibition activity, and catalytic properties of the complexes were investigated as well. The Pd(II) complexes 1b and 1c indicated the best catalytic activity with 62.63% and 61.05% selectivity in the conversions of 82.61% and 87.84%. The in vitro antioxidant activity showed that the Pd(II) complexes, particularly 1a and 1e have effective antioxidant activities. According to the enzyme activity analyses, complex 1b (IC50 value 69.3 +/- 5.2 mu M) showed the most effective pancreatic lipase inhibition, whereas complex 1e (IC50 value 25.7 +/- 3.2 mu M) had the most effective tyrosinase inhibition among the synthesized compounds. Overall, the present paper discusses the synthesis, characterization and catalytic activities of various novel Pd(II)-Schiff base complexes with their antioxidant potentials, pancreatic lipase and tyrosinase inhibitory activities. (C)& nbsp;2022 Elsevier B.V. All rights reserved.
Keywords: Antioxidant; Enzyme inhibition; Pancreatic lipase; Tyrosinase; Mizoroki-Heck; Suzuki-Miyaura Coupling; Pd(II)-Schiff base complexes; Schiff-Base; In-Vitro; Palladium(Ii) Complexes; Pd(Ii); Catalysts; Fe(Ii)